Combining inhibition of galectin-3 with and before a therapeutic vaccination is critical for the prostate-tumor-free outcome. Issue 2 (8th December 2020) - Tiraboschi, Carolina; Gentilini, Lucas; Velazquez, Carla; Corapi, Enrique; Jaworski, Felipe Martín; Garcia Garcia, José Daniel; Rondón, Yorfer; Chauchereau, Anne; Laderach, Diego José; Compagno, Daniel
Abstract : Background: Prostate cancer (PCa) is a major health problem worldwide. Taxol derivatives-based chemotherapies or immunotherapies are usually proposed depending on the symptomatic status of the patient. In the case of immunotherapy, tumors develop robust immune escape mechanisms that abolish any protective response, and to date why prostate cancer is one of the most resistant diseases remains unresolved. Methods: By using a combination of clinical data to study the transcriptome of metastasis samples from patients with castration-refractory prostate cancer, and state of the art cellular and molecular biology assays in samples from tumor-bearing mice that have been submitted to surgical resection of the tumor before receiving a vaccination, we answered several essential questions in the field of immunotherapy for prostate cancer. We also used two different methods to inhibit the expression of galectin-3 (Gal-3) in tumor cells: a stable RNA interference method to control the expression of this galectin efficiently only in tumor cells, and low and non-cytotoxic doses of docetaxel to easily transfer our findings to clinical settings. Results: Herein, we show for the first time that Gal-3 expressed by prostate tumor cells is the main immune checkpoint responsible for the failure of vaccine-based immunotherapy. Our results show that low and non-cytotoxic doses of docetaxel lead to the inhibition of Gal-3 expression in PCa cells as well as in clinical samples of patients with metastatic and castration-resistant PCa promoting a Th1 response. We thus optimized a prostate cancer animal model that undergoes surgical resection of the tumor to mimic prostatectomy usually performed in patients. Importantly, using Gal-3-knocked down-PCa cells or low and non-cytotoxic doses of taxane before vaccination, we were able to highly control tumor recurrence through a direct impact on the proliferation and infiltration of CD8+ cytotoxic T. Conclusions: Thus, Gal-3 expression by PCa cells is a crucial inhibitor for the success of immunotherapy, and low doses of docetaxel with non-cytotoxic effect on leukocyte survival could be used before immunotherapy for all patients with PCa to reduce the expression of this critical negative immune checkpoint, pre-conditioning the tumor-microenvironment to activate an antitumor immune response and promote tumor-free outcome.